2016
DOI: 10.1016/bs.pbr.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cortical fast-spiking parvalbumin-positive basket cells in epilepsy

Abstract: GABAergic interneurons of the parvalbumin-positive fast-spiking basket cells subtype (PV INs) are important regulators of cortical network excitability and of gamma oscillations, involved in signal processing and cognition. Impaired development or function of PV INs has been associated with epilepsy in various animal models of epilepsy, as well as in some genetic forms of epilepsy in humans. In this review, we provide an overview of some of the experimental data linking PV INs dysfunction with epilepsy, focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 337 publications
(258 reference statements)
4
72
0
Order By: Relevance
“…The reduction in cell densities are consistent with previous studies in epileptic rodents (Best et al, 1993;Buckmaster and Dudek, 1997;Dudek et al, 2002;Wyeth et al, 2010;Jiang et al, 2016); however, others have shown a loss of hippocampal PV-expressing cells in tissue obtained from sclerotic patients despite the increase of total neuronal density in the subiculum (Andrioli et al, 2007). Whether the loss of PVand CCK-immunoreactivity is due to cell death or the lack of expression of the neuromarkers is still under debate.…”
Section: Cbd Halts Morphological Pathology Of Two Major Interneuron Ssupporting
confidence: 91%
“…The reduction in cell densities are consistent with previous studies in epileptic rodents (Best et al, 1993;Buckmaster and Dudek, 1997;Dudek et al, 2002;Wyeth et al, 2010;Jiang et al, 2016); however, others have shown a loss of hippocampal PV-expressing cells in tissue obtained from sclerotic patients despite the increase of total neuronal density in the subiculum (Andrioli et al, 2007). Whether the loss of PVand CCK-immunoreactivity is due to cell death or the lack of expression of the neuromarkers is still under debate.…”
Section: Cbd Halts Morphological Pathology Of Two Major Interneuron Ssupporting
confidence: 91%
“…Therefore, PV-positive basket cells are thought to function as “clockworks” for cortical network oscillations, whereas CB1-expressing interneurons operate as a “plastic fine-tuning device.” Perisomatic inhibition has an important role in the generation and regulation of sharp wave-ripples [8], gamma oscillations [9], and seizure-like activities [10] in rodent hippocampal slice preparations. The first attempts have been made to achieve seizure-control via manipulation of perisomatic inhibition in animal models, by selectively stimulate PV-positive neurons and by transplanting interneuron precursors [1113]. However, it is still controversial whether perisomatic inhibition of the human hippocampus is increased or decreased during epileptic conditions [11, 14–16].…”
Section: Introductionmentioning
confidence: 99%
“…Deficits of cortical γ‐aminobutyric acidergic (GABAergic) inhibition lead to severe early onset epilepsy in mice and might contribute to some genetic forms of epilepsy in humans (see reviews). The epilepsy associated with these so‐called “interneuronopathies” is thought to result from a combination of early developmental perturbations in cortical network development and from a persistent failure of local inhibition required to restrain cortical excitation in mature networks . Because epilepsy is refractory to current therapies in nearly one‐third of patients, clarifying the underlying cellular and network mechanisms is required to optimize therapies.…”
mentioning
confidence: 99%